Following resettled people over time: the value of longitudinal data collection for understanding the livelihood impacts of the Three Gorges Dam, China. Issue 1 (2nd January 2017) - Wilmsen, Brooke; van Hulten, Andrew
Abstract: The long-term effects of dam-induced displacement and resettlement are poorly understood. This paper presents a rare longitudinal assessment of the livelihood outcomes of people resettled as a result of a major dam project – the Three Gorges Project in China. It signposts pitfalls that practitioners need to be aware of when planning their own longitudinal monitoring and evaluation (M&E) projects, such as those relating to (i) sample and control group selection, (ii) deciding the timing and frequency of data collection, (iii) mitigating attrition and (iv) accounting for the broader social and policy changes that occur over longer periods when analysing results. The paper argues that longitudinal research is important not only for assessing resettlement outcomes accurately but also for ensuring that ongoing government interventions are adequate and not withdrawn prematurely.